Hyperinflammation in Two Severe Acute Respiratory Syndrome Coronavirus 2-Infected Adolescents Successfully Treated With the Interleukin-1 Inhibitor Anakinra and Glucocorticoids - Calò Carducci, Francesca I.; De Ioris, Maria Antonietta; Agrati, Chiara; Carsetti, Rita; Perrotta, Daniela; D'Argenio, Patrizia; De Benedetti, Fabrizio; Notari, Stefania; Rossi, Paolo; Campana, Andrea (Frontiers in Pediatrics, 2020)
Background: In severe acute respiratory syndrome-related coronavirus (SARS-CoV-2) critically ill adults, hyperinflammation plays a key role in disease progression. The clinical manifestations of SARS-CoV-2 infection among children are much less severe compared to adult patients, and usually associated with a good prognosis. However, hyperinflammation in SARS-CoV-2 infected pediatric patients has been described as pediatric inflammatory multisystem syndrome temporally associated with SARS-CoV-2 or as Kawasaki-like disease but is still little known and optimal management has to be defined. WHO 15th of May stated for an urgent need to collect data on this condition. Here we report two adolescent patients affected by COVID 19 presenting with hyperinflammation, three to four weeks after first symptoms of SARS-CoV-2 infection, treated with the IL-1 receptor antagonist anakinra and glucocorticoids with good clinical response. Case presentation we reported two patients, with history of ascertained SARS-CoV-2 infection, who presented three to four weeks after first symptoms of infection with high fever, poor general conditions, severe gastrointestinal involvement and increased biomarkers of inflammation and proinflammatory citokines serum level. They had no lung involvement but abdominal ultrasound and CT scan showed thickening of the bowel wall. SARS-CoV-2 PCR was positive on ileum biopsy in both patients, whereas was negative on other common sampled sites. They have been admitted to pediatric intensive care unit and have been treated with combination of anakinra 6-8 mg/kg/die iv and a standard dose of methylprednisolone 2 mg/kg/die in addition to lopinavir/ritonavir 400 mg q12h and low molecular weight heparin 100 UI/kg q12h with good clinical response Conclusion: our report demonstrates the occurrence of cytokine storm and hyperinflammation in some children infected by SARS-CoV-2, the late onset of this potential complication and the effectiveness of immune-modulating therapy. This atypical presentation of pediatric patients should be always taken into consideration during the pandemic in order to ensure prompt diagnosis and appropriate therapeutic management.